Evaluation of oral health education puppet shows conducted by 3rd year dental students, Dental Faculty of International Islamic University Malaysia - Abllah, Zurainie; Tin, Myo Han; Yakop, Noraini (2013)
Objective: To assess the effectiveness of oral health education (OHE) puppet shows conducted by 3rd Year dental students to preschool children Methods: A face to face interview was carried out among 101 preschool children (4-6 years old) to assess the perception and receiving OHE information on sweet consumption, tooth brushing, suffering tooth ache and visiting a dentist after 4 OHE puppet shows conducted by 3rd year dental students at Dental Faculty of International Islamic University, Malaysia in 2013 .The scripts and performances of the OHE puppet shows were graded as good, acceptable and need to be improved based on contents and performance. A cross analysis was done between the scripts and performances of the puppets shows and OHE information received by the preschool children. Results: Among 4 scripts and performances of OHE puppet shows, one was graded as good, two were acceptable and one was need to be improved. Out of 101 preschool children, 61% of them liked too much OHE puppet shows and 38% just liked it. Sixteen percents of preschool children recall back three or all of four facts of OHE information, 66% recalled one or two facts and 18% could not remember any fact. Association between grading of the script and performance of the puppet shows and receiving OHE information by preschool children was noticed (p<0.05). Conclusion: This evaluation proved that there was some extent of effectiveness of OHE puppets among preschool children. A proper coaching to dental students is needed to produce effective OHE puppet shows. (Total Word Count- 250)